Checklist of Indian mites in the family Laelapidae (Acari: Mesostigmata) - Bandyopadhyay, Pritha; Karmakar, Krishna; Halliday, Bruce (Zootaxa, 2023)
Laelapidae Canestrini, 1891 is one of the most diverse mite families in the order Mesostigmata, but the Indian fauna of this family is very poorly known. This paper is a checklist of the known species of Laelapidae recorded from India, with a summary of the available information on the distribution and biology of each species. The known fauna includes 66 species in 21 genera, plus seven species whose generic placement is unresolved and a number of others that lack validly published descriptions.